Synthesis and Antitumor Evaluation of Novel 5-Bromo Indole-Aryl Keto Hydrazide-Hydrazone Analogues - Rudavath, Durgesh; Sreenivasulu, Reddymasu; Pinapati, Srinivasa Rao; Raju, Rudraraju Ramesh (Asian Journal of Chemistry, 2018)
A wide variety of indole, substituted benzaldehyde linked keto hydrazide-hydrazone analogues were designed, synthesized and evaluated for their cytotoxicity against eight human cancer cell lines HeLa, A549, MCF-7, K562, HEK293, HT29, SF295 and HL60. All these synthesized compounds showed potent antitumor activities on the above eight human cancer cell lines. Among them, 6a and 6h compounds exhibited potent antitumor activity on HL 60 and A549 cancer cell lines with IC50 value of 3.913 and 4.838 μM than the standard drug cisplatin with IC50 values of 27 and 36 μM, respectively.